Análise da gravidez repetida na adolescência em uma região do meio Norte Brasileiro - ALMEIDA, Larissa Maciel de (2022)
Introduction: Repeated pregnancy in adolescence is a phenomenon that interferes with the social representations of adolescents, thus, often conditioned by physical, emotional, social and economic unpreparedness, which can compromise the performance of maternal functions. Objective: To analyze repeated pregnancy among adolescents in a region of the middle north of Brazil. Methods: Cross-sectional, descriptive and analytical epidemiological study with a quantitative approach carried out with 124 adolescent mothers between 10 and 19 years old in the city of Caxias - MA. A questionnaire with questions about sociodemographic, economic, obstetric and lifestyle data was applied. Results: Among the 124 adolescents, 107 (86.3%) were older than 15 years; 104 (83.9%) had studied for more than 8 years; 72 (58.1%) did not have a partner and 113 (91.1%) did not have a job. More than half (N=64; 51.6%) of the adolescents started their sexual life when they were 15 years old or younger; 110 (88.7%) had no previous abortions; 107 (86.3%) denied the desire to terminate the pregnancy; 105 (84.7%) said they had not changed partners in the year and 02 (1.6%) reported experiencing sexual violence. The prevalence of repeated pregnancy was 34.7% (N=43), statistically associated with the number of deliveries (p<0.000; OR: 17.62; 95%CI: 6.51-47.68) and the desire to interrupt the pregnancy. pregnancy (p=0.047; OR: 3.20; 95%CI: 1.12-9.15). Education level was a protective factor (p=0.012; OR: 0.28; 95%CI: 0.11-0.76) for repeated pregnancy. Conclusion: Adolescents who had one or more deliveries and a desire to terminate the pregnancy were more likely to have a new pregnancy. Those with higher education were less likely to have a repeat pregnancy. This result prioritizes better planning of assistance from the health and nursing team of Health Primary Care to adolescent users.